Científicos en 90 minutos. (Pack 2), (Turing y el ordenador, Crick, Watson y el ADN, Oppenheimer y la bomba atómica, Pitágoras y su teorema, Darwin y la evolución, y Arquímedes y la palanca) - Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940- (Tres Cantos, Madrid, España : Siglo XXI de España Editores, S.A., 2017)
The Científicos Pack 2 gathers 6 of the most outstanding scientists in history. Paul Strathern presents an accurate and expert account of the life, ideas and discoveries of these six scientists and explains their influence on man's struggle to understand his existence in the world.
Turing y el ordenador en 90 minutos -- Crick, Watson y el ADN en 90 minutos -- Oppenheimer y la bomba atómica en 90 minutos -- Pitágoras y su teorema en 90 minutos -- Darwin y la evolución en 90 minutos -- Arquímedes y la palanca en 90 minutos.
This collection of books by Strathern were published separately in print. The publisher now combined them by subject and published them together in digital format.
Includes bibliographical references.
Online resource; title from ePub title page (Digitalia, viewed February 7, 2019)
Keywords: Turing, Alan, -- 1912-1954.; Crick, Francis, -- 1916-2004.; Watson, James D., -- 1928-; Oppenheimer, J. Robert, -- 1904-1967.; Pythagoras; Darwin, Charles, -- 1809-1882.; Archimedes; Scientists -- Biography; Biographies; Electronic books